Shark variable new antigen receptor biologics – a novel technology platform for therapeutic drug development. (October 2014) - Kovaleva, Marina; Ferguson, Laura; Steven, John; Porter, Andrew; Barelle, Caroline
Abstract : Introduction: Biologics drugs have succeeded in achieving a commercial dominance in the global market for new therapies and large pharmaceutical companies' interest remains strong through a continued commitment to pipeline development. It is not surprising, therefore, that next-generation biologics, particularly antibody-like scaffolds that offer many of the advantages of the original biologic drugs but in simplified formats, have entered the clinic as competing substitute therapeutic products, to capture market share. Areas covered: Specifically, this paper will position shark-derived variable new antigen receptors (VNARs) within an overview of the existing biologics landscape including the growth, diversity and success to date of alternative scaffolds. The intention is not to provide a comprehensive review of biologics as a whole but to discuss the main competing single-domain technologies and the exciting therapeutic potential of VNAR domains as clinical candidates within this context. Expert opinion: The inherent ability to specifically bind target and intervene in disease-related biological processes, while reducing off-site toxicity, makes mAbs an effective, potent and now proven class of therapeutics. There are, however, limitations to these 'magic bullets'. Their size and complexity can restrict their utility in certain diseases types and disease locations. In contrast, a number of so-called alternative scaffolds, derived from both immunoglobulin- and non-immunoglobulin-based sources have been developed with real potential to overcome many of the shortcomings documented for mAb treatments. Unlike competing approaches such as Darpins and Affibodies, we now know that shark VNAR domains (like camel VHH nanobody domains), are an integral part of the adaptive immune system of these animals and have evolved naturally (but from very different starting molecules) to exhibit high affinity and selectivity for target. In addition, and again influenced by the environment in which they have evolved naturally, their small size, simple architecture, high solubility and stability, deliver additional flexibility compared to classical antibodies (and many non-natural alternative scaffolds), thereby providing an attractive basis for particular clinical indications where these attributes may offer advantages.